Impact of Different Extraction Methods on Furanosesquiterpenoids Content and Antibacterial Activity of Commiphora myrrha Resin - Ali S. Alqahtani; Rashed N. Herqash; Omar M. Noman; Md. Tabish Rehman; Abdelaaty A. Shahat; Mohamed F. Alajmi; Fahd A. Nasr (Journal of Analytical Methods in Chemistry)
The oleo-gum-resin of Commiphora myrrha is one of the most known natural antimicrobial agents, mainly due to its furanosesquiterpenes. A validated method based on sample extraction by matrix solid-phase dispersion (MSPD) followed by high-performance column chromatography (HPLC) determination is applied to analyze two furanosesquiterpenoids, namely, 2-methoxyfuranodiene (CM-1) and 2-acetoxyfuranodiene (CM-2), existing in C. myrrha. The trial parameters that controlled the extraction prospective were studied and optimized. These include the nature of dispersant, mass ratio of sample to the dispersant, and the volume of elution solvent. A comparative antimicrobial study that used the Minimum Inhibitory Concentration Assay (MIC) method between MSPD, ultrasonic, and Soxhlet of myrrh extracts was also conducted. The optimal MSPD parameters used were (i) 15 mL of methanol applied as elution solvent; (ii) silica gel/sample mass at a 2 : 1 ratio; and (iii) a dispersing sorbent selected as silica gel. Technique retrievals were regulated from 96.87% to 100.54%, with relative standard deviations (RSDs) from 1.24% to 4.45%. Commiphora myrrha-MSPD (CM-MSPD) extract showed the highest antibacterial activity against gram-positive and gram-negative bacteria (156.25 μg/mL and 312.5 μg/mL, respectively) and antifungal activity (156.25 μg/mL). Yields acquired through the MSPD technique were larger than yields from other extraction techniques (sonication and traditional reflux extraction methods) with less consumption of time, sample, and solvent. The mode of antibacterial action of CM-1 and CM-2 was elucidated by performing molecular docking with bacterial DNA gyrase. Both the compounds interacted with key residues of DNA gyrase.